Sporadic Colorectal Tubular Adenomas Thrive in Symbiosis With Underlying Nondysplastic Branching Crypts - Rubio, Carlos A.; Matek, Christian; Vieth, Michael; Lang-Schwarz, Corinna (Anticancer Research, 2023)
BACKGROUND/AIM: Nondysplastic crypt branching (NDCB), mostly asymmetric branching (NDCAB), was previously found beneath the dysplastic epithelium of colorectal tubular adenomas (TA) in Swedish patients. This study examined the frequency of NDCB and NDCAB beneath the dysplastic epithelium of TA, in German patients. PATIENTS AND METHODS: From a collection of 305 TA, 121 TA fulfilled the prerequisites for inclusion. All NDCB were registered. RESULTS: Of 673 NDBCs, 572 (85%) NDCABs and 101 (15%) NDCSs, were found beneath the neoplastic tissue in the 121 TA. When the frequency of NDCB was challenged against the TA size, a linear correlation was found in the 121 TA (p<0.05, p=0.020172). Most NDCB were NDCAB (p<0.05, p=0.00001). The frequency of NDCB correlated with increasing TA size, implying that the higher frequency of both NDCB, dysplastic crypt branching, and their dysplastic offspring crypts were the most probable sources of TA enlargement. The frequency of NDCB underneath TA was not influenced by increasing age, sex or TA localization. CONCLUSION: Similar findings as those reported here were previously found in TA in Swedish patients. The similarity between these two populations, located in disparate geographical areas and subjected to dissimilar microenvironmental conditions suggests that NDBC in TA might be a ubiquitous unreported phenomenon. According to the literature, normal colon cells often harbor somatic mutations. Consequently, NDCB underneath TA may be mutated nondysplastic branching crypts upon which the dysplastic epithelium in TA eventually develops.
CRIS-Team Scopus Importer:2023-11-17
Keywords: abnormal branching; Colon; nondysplastic colon crypts; rectum; tubular adenomas